Riverflow : the right to keep water instream / Paul Stanton Kibel, Golden Gate University School of Law. - Kibel, Paul Stanton (Cambridge University Press, 2021)
There are many people and places connected to rivers: fishermen whose livelihood depends on river ecosystems, farms that need irrigation, indigenous groups whose cultures rely on fish and flowing waters, cities whose electricity comes from hydroelectric dams, and citizens who seek wild nature. For all of these people, instream flow is vitally important to where and how they live and work. Riverflow reveals the diverse and creative ways people are using the law to restore rivers, from the Columbia, Colorado, Klamath and Sacramento-San Joaquin watersheds in America, to the watersheds of the Tweed in England and Scotland, the Fraser in Canada, the Saru in Japan, the Nile in North Africa, and the Tigris-Euphrates in the Middle East. Riverflow documents that we already have the legal tools to preserve the ecological integrity of our waterways; the question is whether we have the political will to deploy these tools effectively.